AUTOMATIC SECURITY SYSTEM IN BHAYANGKARA INDAH OFFICE FROM THEFT, GAS LEAKAGE, AND FIRE AND FLOOD BASED ON ARDUINO NANO - Sutan Hirmansyah Siregar; Rolly Yesputra; Sahren Sahren (Informatika, Universitas Jenderal Soedirman, 2022)
The office is a very necessary place to work, where an office must provide a sense of security to employees. At the Bhayangkara Indah office, theft often occurs because there is no security guard guarding the office and there are often sudden floods that cause the goods and facilities in the office to be submerged and there is no security system that informs the occurrence of gas leaks that can cause fires. The purpose of this study was to determine flooding using the yl-69 sensor in the event of a flood, to determine gas leaks using the MQ-7 sensor in the event of a gas leak and the use of RFID as a tool to access security on the door of the house and to detect fire using the Flame sensor. in case of fire. The test results are carried out with a direct trial phase to measure the level of performance of the sensors used. It is hoped that with this research, the design of a security device that is made can help maintain security at the Bhayangkara Indah Housing office to find out if there is a flood, gas leak, fire, and theft.